Building on Success in Tobacco Control: A Roadmap Towards Tobacco-Free Oman (Perspective Review) - Salma R. AlKalbani; Paul Kavanagh (Journal of Public Health International, 2023)
Tobacco use remains a leading cause of harm to public health. Despite nearly two decades of ratifying the WHO Framework Convention on Tobacco Control (FCTC), Oman is still striving to achieve the best practice approach in different FCTC measures. Current epidemiological data shows that the prevalence of tobacco use among adults in Oman is steadily increasing with time. This review highlights the progress that has been made in the various FCTC measures, as well as how Oman has the possibility to attain the best practice approach in the various FCTC measures, and even go beyond that by implementing policies that have the potential to achieve a tobacco-free Oman by 2040.
Keywords: Tobacco use